INFECTIUS DERMATITIS IN CANINES - Ceino-Gordillo, Franco (2021)
Dermatitis is a general term describing an irritation of the skin which has various causes and forms. It currently aff ects many canines in homes and on the streets. Th e pathogens that cause this condition cause severe lesions in the dermis, epidermis and hypodermis. According to studies developed in several veterinary clinics in Perú, it is known that infectious dermatitis is the most prevalent in canines. Among the most frequent agents, bacteria and fungi such as Staphylococcus, Dermatophytes and Malassezia were found.